Individual investors and social ownership structures in the UK before the 1930s: Joint holdings and trustee investment. (28th September 2022) - Rutterford, Janette; Sotiropoulos, Dimitris P.; van Lieshout, Carry
Abstract: After the introduction of limited liability, a growing number of individuals in Britain from a widening social spectrum, including the less affluent, began to own stocks and shares. Drawing upon a unique and large dataset of 35 848 investors between 1870 and 1935, this study analyses joint holdings which have been a neglected aspect of investor behaviour. Our findings reveal that joint holdings were quite common and that about one in five UK investors were involved in a joint investment. Men were more likely to be joint holders than women for reasons related to institutions of social ownership such as trusts and executorships.